Thematic Progression Analysis in Different Gender and Major by Students Of 12th Grade in Writing Review Text - Junianti Naibaho; Arsen Nahum Pasaribu; Erika Sinambela (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
The present research was conducted to analyze the thematic progression in students’ writing review text at grade 12 at SMA N 12 Medan. Therefore this research was led to analyze the kinds of thematic progression used by the students in writing review text and to find out how thematic progression was realized in students writing review text. Descriptive Qualitative was applying in this research. This research conducted for twelve grade of science and social class, male and females students’ consist of (5 males + 5 females students from Science class) and ( 5 males + 5 females students from social class). The result shows the researcher found that both in social and science class, all of the thematic progression are found in the passage which written by them. The first the researcher found the Reiteration Theme or Constant theme in almost every passage that written by the students and it is same if the researcher compared it by Male and Female class. It means that the students in social and science class even male and female trying to keep their passage is coherence each other. Then also find Zig Zag theme, almost every students already able to build an information but still has a cohesion with another sentence. The last the researcher also found the multiple rheme pattern. It shows that the students able to build a lot of information from the first rheme.